Thrombo-angitis obliterans: a clinico-pathological study - Sachin, Idoor D.; Manasa, Megaravalli R. (International Surgery Journal, 2016)
Background: Thrombo-angitis obliterans (TAO) is a disease of young and middle aged individuals who are addicted to smoking from early teens. Greater awareness should be created among the general population regarding smoking, as it is the major cause of TAO. Early diagnosis and management is essential as it is a self limiting disease with complete cessation of smoking. Methods: 50 patients of TAO were selected based on inclusion and exclusion criteria. Data was collected by history, clinical examination and radiological investigation. Patients were treated with conservative management, lumbar sympathectomy, cervical sympathectomy, disarticulation and amputation. Results: Majority of the patients were in the age group of 30-40 years. All the patients were males belonging to low socio-economic status and chronic smokers. Most of them had right lower limb involvement and presented with rest pain with intermittent claudication. Majority of them were manual workers. 80% of the patients had low temperature in the affected limb. 96% of the patients had dorsalis pedis and posterior tibial arteries involvement. 44 patients underwent lumbar sympathectomy. Ischaemic ulcer healed in 56% of these patients, colour changes improved in 78% and rest pain improved in 42%. Conclusions: TAO was common in males aged 30-40 years belonging to low socio-economic status. Lower limb was commonly involved. Smoking has a definite role in the development of TAO. Pain was the predominant complaint. Manual labourers were commonly affected. Medium to small calibre vessels were involved. Majority of the patients were treated by lumbar sympathectomy.